Efeito do jejum e da insulina exógena sobre parâmetros metabólicos e expressão gênica do receptor do hormônio do crescimento (GH) e fator de crescimento semelhante à insulina tipo I (IGF-I), no folículo préovulatório de ovelhas - Schneider, Augusto (2008)
In non-ovarian tissues GHR expression is regulated by insulin concentrations and is correlated to IGF-I expression. In the ovary IGF-I expression is also related to insulin levels, however no correlation with GHR was demonstrated until now. The aim of this study was to investigate the effect of fasting or insulin administration on blood concentrations of glucose, nonsterified fatty acids, insulin, insulin like growth factor I (IGF-I) and estradiol and on follicular expression of growth hormone receptor (GHR) and IGF-I mRNA in ewes. Fifteen ewes received an intravaginal progesterone releasing device that was removed 6 days later (Day 0). In Day -2 the ewes were divided in: control group, which received maintenance diet, insulin group, which received insulin injections every 12 hours from Day -2 to 2 and fasting group, which was submitted to fasting from Day -2 to 2. The results of the current study revealed that insulin administration or fasting during the development of a follicular wave did not affect (P=0.22) follicular diameter, although insulin injection increased (P=0.02) estradiol production. There was no difference among groups for GHR or IGF-I mRNA expression in granulosa (P=0.62, 0.43) or theca cells (P=0.92, 0.43). For fasting group there was a positive correlation between glucose and estradiol (r=0.97, P=0.006) and granulosa cell IGF mRNA (r=0.96, P=0.03). For insulin group estradiol was positive correlated to follicular diameter (r=0.93, P=0.02) and granulosa cell GHR (r=0.87, P=0.05) and IGF-I mRNA (r=0.79, P=0.10). In conclusion, exogenous insulin or fasting did not affect follicular diameter and expression of GHR and IGF-I mRNA in the pre-ovulatory follicle, although exogenous insulin increased estradiol production.